ELASTISITAS HASIL TANGKAPAN UDANG MANTIS (Harpiosquilla raphidea) DENGAN MESH SIZE DAN PANJANG JARING INSANG DI KELURAHAN KAMPUNG NELAYAN KUALA TUNGKAL - Triani, Sindi; Firmansyah, Firmansyah; Hariski, M.; Alwi, Yun; Arfiana, BS Monica; Wulandari, Wulandari (Universitas Mataram, 2025)
The fishing gear used by fishermen in catching mantis shrimp is a gillnet. The purpose of the study was to determine the elasticity of mesh size and net length to the production of mantis shrimp catch. The gillnet used in this study has a mesh size of 3.5 inches and 4 inches and a net length of 900 m, 1050 m and 1200 m. The method used in this study is a survey, and the data analysis used is the Cobb Douglas production function using SPSS version 26 and subsequently in the elasticity analysis. The results of the descriptive study both in number and composition show that the production of mantis shrimp catch based on mesh size in Kuala Tungkal waters is the most using a size of 4 inches, which is as many as 480 fish or 50.57%, while based on the length of the net, the most is using a size of 1,200 m, which is 419 fish or 45.15%. Simultaneous analysis of the signification obtained was 0.00 < 0.05, meaning that the mesh size and net length together had a significant influence on the production of mantis shrimp catch, while partially the significance value for the mesh size was 0.00 < 0.05 and the net length also had a significance of 0.00 < 0.05 which means that the mesh size and net length had an effect on the production of mantis shrimp catch. Based on the elasticity analysis, the value of the parameter coefficient of the cobb douglas regression equation is 1.229 or greater than 1, which means that the production of mantis shrimp catch is included in the category of increasing return to scale or the change in output obtained will be greater than the input used